The Transformational Leadership, Intellectual Capital, and Work Environment as Determinants of Employee Performance: Evidence from Company X - Muhammad Tahajjudi Ghifary; Dyajeng Puteri Woro Subagio (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2026)
This study examines the role of transformational leadership, intellectual capital, and the work environment as key determinants of employee performance in a corporate setting, using empirical evidence from Company X. Drawing on leadership theory and the resource-based view, the research investigates how managerial practices and intangible organizational resources contribute to performance improvement. A quantitative research design was employed with a census sampling technique involving 40 employees, and data were collected through structured questionnaires. The analysis was conducted using multiple linear regression, supported by validity, reliability, and classical assumption tests. The results reveal that transformational leadership and intellectual capital have a positive and statistically significant effect on employee performance, while the work environment also demonstrates a significant influence, indicating the importance of both physical and psychosocial workplace conditions. Collectively, these variables explain a substantial proportion of variance in employee performance, underscoring their strategic relevance in organizational performance management. The findings contribute to the empirical literature by providing evidence from a corporate context in a developing economy and offer practical implications for organizations seeking to enhance employee performance through leadership development, effective intellectual capital management, and the creation of a supportive work environment.